2014
DOI: 10.1038/nchem.2024
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric triplex metallohelices with high and selective activity against cancer cells

Abstract: These authors contributed equally to this work An antiparallel strand arrangement in water-soluble helicates creates an amphipathic functional topology akin to that of host-defence peptides. High and selective cancer cell line toxicity is exhibited, causing dramatic changes in the cell cycle without DNA damage, and remarkably there is no significant toxicity to MRSA and E. coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
99
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 49 publications
0
99
0
2
Order By: Relevance
“…The triple helicate exhibited specific interaction with DNA and showed antimicrobial activity; the Λ enantiomer had greater binding affinity with DNA, produced greater stabilization of the DNA duplex, and exhibited greater antimicrobial activity than the corresponding Δ enantiomer [66]. The corresponding triple helicate exhibited high, stereodependent toxicity to human colon cancer cell lines, but no significant toxicity to Gram-positive and Gram-negative bacteria [67]. The dinuclear helicates also exhibited enantioselective inhibition of amyloid-β aggregation [68].…”
Section: Dynamic Production and Inversion Of Supramolecular Chiralitymentioning
confidence: 93%
“…The triple helicate exhibited specific interaction with DNA and showed antimicrobial activity; the Λ enantiomer had greater binding affinity with DNA, produced greater stabilization of the DNA duplex, and exhibited greater antimicrobial activity than the corresponding Δ enantiomer [66]. The corresponding triple helicate exhibited high, stereodependent toxicity to human colon cancer cell lines, but no significant toxicity to Gram-positive and Gram-negative bacteria [67]. The dinuclear helicates also exhibited enantioselective inhibition of amyloid-β aggregation [68].…”
Section: Dynamic Production and Inversion Of Supramolecular Chiralitymentioning
confidence: 93%
“…Additionally, Hannon and co-workers found that these tetracationic iron(II) cylinders display both anti-cancer [19] and anti-bacterial properties [20]. The biological properties of other related helicate systems have also been examined, these molecules can bind to G-quadruplex DNA [21][22][23], inhibit Ab amyloid aggregation [24,25] and also show cytotoxic (anti-cancer [26][27][28] and anti-bacterial [28]) properties.…”
Section: Introductionmentioning
confidence: 95%
“…This kind of selectivity is very unusual and indicates a subtle biomimetic mechanism. Dramatic effects on the cell cycle and the promotion of early apoptosis were observed, but no DNA damage was detected in a range of studies . Flexicates do not damage DNA in cancerous cells like many traditional agents but act by inducing cell cycle arrest and apoptosis.…”
Section: Introductionmentioning
confidence: 99%